Reference Criteria For Forehand Shot In Badminton According To Performance Time And Accuracy Of Middle and South Club Players U17 - Shihab, Zehra; Jalab, Mohammed (Journal of Physical Education, 2015)
The importance of the research lies in designing reference criteria for forehand shot in badminton according to performance time and accuracy. The problem of the research was that all tests designed by previous researchers concentrate on accuracy only, the researchers proposed the necessity of building a test according to accuracy and time of performance so as to combine skill performance tests with skill performance during competition. The researchers used the descriptive method. The results showed that the tests prepared by the researchers can be used to test middle and south governorate Badminton players under 17. Finally the researchers recommended using these tests during badminton players’ selection by the national badminton federation.